PENGARUH VARIASI BAHAN BAKAR VIVO DAN SHELL DENGAN OKTAN 92 DAN 95 TERHADAP PERFORMA SEPEDA MOTOR YAMAHA MIO 150 CC - R. Lutfi Zakaria; M Reja Awaludin (Bajang Institute, 2024)
Currently, public vehicles such as motorbikes use several types of fuel, including fuel from Vivo and Shell companies apart from Pertamina. Motorcycle engine performance is influenced by several factors, including the type of fuel used. Many people do not know the effect of using this fuel (Vivo and Shell) which has RON 92 and RON 95 on the engine itself due to a lack of understanding of the properties of the fuel. Therefore, the author intends to conduct research on the analysis of the influence of RON 92 and RON 95 fuel from Vivo and Shell products on the performance of the Yamaha Mio 150 cc reciprocating engine in order to obtain optimum fuel. This research aims to determine the difference in motor performance when using Vivo and Shell fuel by testing torque, power, and then analyzing specific fuel consumption. The tests for each type of fuel were Revvo 92, Revvo 95, Shell Power 92 and Shell V-Power 95 which were tested on a 150 cc Yamaha Mio motorbike engine